1991
DOI: 10.1093/ageing/20.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Femoral Fractures in the Elderly: Does Operative Delay for Medical Reasons Affect Short-term Outcome?

Abstract: Forty patients over 65 years of age with fractures of the proximal femur, whose operation was delayed more than 24 hours after admission for medical reasons, were studied. Length of post-operative stay on the orthopaedic wards, mobility after one month and need for continuing supervision by the geriatric services, after discharge from the orthopaedic wards, were compared with a matched group in whom there was no delay. There were no significant differences between the results of the two groups, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Harries and Eastwood specifically looked into post-operative length of stay and could not identified any relationship with surgeries done within 24 h [42]. Ho et al also revealed the waiting time for surgery was not a significant predictor of post-surgery length of stay when confounding factors were controlled [43].…”
Section: Resultsmentioning
confidence: 99%
“…Harries and Eastwood specifically looked into post-operative length of stay and could not identified any relationship with surgeries done within 24 h [42]. Ho et al also revealed the waiting time for surgery was not a significant predictor of post-surgery length of stay when confounding factors were controlled [43].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen of these citations proved eligible for inclusion 8,12,15,[22][23][24][25][26][27][28][29][30][31][32][33][34] (Figure 1). Two studies were possible duplicates, but we included both in our analysis because one assessed long-term mortality 24 and the other assessed shortterm mortality.…”
Section: Studies Includedmentioning
confidence: 99%
“…We judged four studies 8,[32][33][34] to be of high methodologic quality, five studies 15,22,24,27,31 to be of moderate quality and the remaining seven studies 12,23,25,26,[28][29][30] to be of low quality (Table 1). Agreement between reviewers in the assessment of study quality was excellent (intraclass correlation coefficient 0.92, 95% CI 0.75-0.97).…”
Section: Study Qualitymentioning
confidence: 99%
“…There is a reduced incidence of avascular necrosis of the femoral head and nonunion, morbidity and mortality, and of complications including decubitus ulcers, urinary tract infections, and deep vein thrombosis (DVT). [15][16][17][18][19][20][21][22][23][24][25] However, the data about mortality in this group of patients is conflicting. In a retrospective study of 6638 patients with a fracture of the hip, Bretherton and Parker 19 found that surgery 12 hours or later after admission to hospital had a 1.59-times increased odds of 30-day mortality when compared with surgery within 12 hours of admis-sion.…”
mentioning
confidence: 99%